2002
DOI: 10.1590/s0103-90162002000400019
|View full text |Cite
|
Sign up to set email alerts
|

Use of AFLPS to distinguish landraces of pejibaye (Bactris gasipaes) in brazilian Amazonia

Abstract: Although the first inhabitants of western Amazonia domesticated pejibaye (Bactris gasipaes Kunth, Palmae) or peach palm for its fruits, today it is widely planted for its heart-of-palm. Like other domesticates, pejibaye presents a complex hierarchy of landraces developed before the conquest of the Americas. The existence of three landraces (Pará, Solimões, Putumayo) was proposed along the Amazonas and Solimões Rivers, Brazil, based on morphological characteristics. There are some questions remaining about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
(2 reference statements)
1
11
0
2
Order By: Relevance
“…In studies on the palm species Euterpe edulis, Cardoso et al (2000) used five primer pairs and found 429 fragments of which 395 (92 %) were polymorphic. To evaluate the existence of three races of peach palm, a domesticated species, Clement et al (2002) used six primer combinations generating 245 fragments, of which 135 (55.1n%) were polymorphic.…”
Section: Resultsmentioning
confidence: 99%
“…In studies on the palm species Euterpe edulis, Cardoso et al (2000) used five primer pairs and found 429 fragments of which 395 (92 %) were polymorphic. To evaluate the existence of three races of peach palm, a domesticated species, Clement et al (2002) used six primer combinations generating 245 fragments, of which 135 (55.1n%) were polymorphic.…”
Section: Resultsmentioning
confidence: 99%
“…Também estes dados discordam de resultados obtidos com técnicas moleculares e isoenzimas (Picanço et al, 1999;Gallego Rodrigues et al,1999;Rodrigues, 2001;Clement et al, 2002;Sousa et al, 2002), onde concluíram que a raça Solimões não existe. As três técnicas estatís-ticas multivariadas mostraram, em conjunto, ser um método eficiente de discriminação das raças Pará, Putumayo e Solimões.…”
Section: Resultsunclassified
“…Trabalhos realizados com biologia molecular, para verificar a existência das três raças (Rodrigues, 2001;Clement et al, 2002;Souza et al, 2002), negam a existência da raça Solimões. Quando se deseja discriminar grupos ou populações, Sokal (1965) e Sneath & Sokal (1973) afirmam que a seleção das características é fundamental.…”
Section: Introductionunclassified
“…While validation of morphometrically defined landraces has been a preoccupation of the molecular genetic analyses in the Brazilian germplasm bank (Sousa et al, 2001;Clement et al, 2002;Rodrigues et al, 2005;Cristo-Araújo et al, 2010;Santos et al, 2011), these analyses often had insufficient or unbalanced numbers of each population to work with. When sufficient numbers were available, they validated some landraces and did not validate others, specifically the Guatuso and Tuira landraces in Central America, and the Solimões landrace in central-western Amazonia (Rodrigues et al, 2005).…”
Section: Dispersal Of the Landrace Complexmentioning
confidence: 99%